A Study Comparison the Application of Discovery Learning and Problem Based Learning Models on the Critical Thinking Ability - Muhammad Akhir; Jodion Siburian; Muhammad Haris Effendi Hasibuan (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The purpose of this study is how are the differences in students' critical thinking skills in physics subjects using discovery and problem-based learning models at Madrasah Aliyah Laboratory in Jambi City. Methodology: The research design used by researchers is a quantitative research type of quasi-experimental design using a pretest-posttest control group design, with a total sample of 56 students using a total sampling technique. The instrument in this study used a test with a Cronbach alpha of 0.919. The data analysis used includes descriptive and inferential statistics. Main Findings: Based on the data analysis and discussion above, it can be concluded that students' critical thinking skills in physics subjects in static electricity material are in a good category. This indicates that the application of discovery learning models and problem-based learning can improve the thinking skills of critical students. This is reinforced by testing the hypothesis through an independent sample t-test that there is a significant difference between the use of the two models in improving students' critical thinking skills, especially in physics lessons on static electricity. Novelty/Originality of this study: This research has a novelty, especially in cognitive, namely critical thinking skills, which can be improved with a scientific approach, especially using discovery learning models and problem-based learning.